Implementation Of The Strong Coastal Development Program In The Efforts To Develop Coastal Areas As Poverty Reduction Efforts In Central Java Province - Kundori Kundori; Arika Palapa (Majalah Ilmiah Bahari Jogja, 2021)
Coastal villages have different characteristics from villages in rural areas. This difference is not only on the geographical-ecological aspect, but also on economic and socio-cultural characteristics. Geographically, coastal villages are on the border between land and sea. Geographical-ecological conditions of coastal villages affect economic activities in them. Economic activities in coastal villages are characterized by activities in the utilization of coastal environmental resources and services. Economic activities include fisheries, trade, maritime tourism, and transportation This study seeks to study the application of tough coastal development programs as an effort to build an oriented coastal region to facilitate the economic activities of villages in coastal areas that are expected to reduce the poverty rate of coastal communities in the middle of the city. This study uses a qualitative research design using descriptive methods that intend to explain how the phenomenon of resilient coastal village development and coastal area development as an effort to reduce the number of coastal communities in Central Java province by using purposive sampling sampling techniques and research samples taken in coastal communities The results of the north coast of Java and cilacap districts were as follows: that the implementation of the strong Coastal Village Development Program in the coastal communities of Central Java showed that the three focuses of development activities had been carried out properly. The development activities are resource development, environmental / infrastructure development, and disaster preparedness development. While activities that are not carried out are human development and business development. The recommendations given in this study are that the implementation of the program must be supported by sufficient funds, need coordination and cooperation with other stakeholders, and the need for effective monitoring and evaluation Keywords: program implementation, coastal village, coastal area development, Poverty, Central Java